(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Tinospora cordifolia stems (T. cordifolia), commonly known as Guduchi, is an effective Ayurveda drug used for diabetes management and various other disorders and ailments. Guduchi satva is classical Ayurvedic medicine being used for the treatment of diabetes and a variety of other disorders. The present study was conceded to determine the aqueous extract of T. cordifolia and Guduchi satva formulation for their relative identification of secondary metabolites using physicochemical parameters, fourier-transform infrared spectroscopy (FTIR) fingerprint, and GCMS profiling. In vitro enzyme inhibition assay on α amylase and α glucosidase were also evaluated for both the extracts, in which Guduchi satva possess enhanced inhibition of enzymatic activity over the aqueous extract of T. cordifolia. The phytochemical and FTIR investigations were confirmed for the presence of alkaloids, tannins, carbohydrates, flavonoids, steroids, aromatic, hydroxy, and nitrogen-containing compounds. The gas chromatography mass spectrometry (GCMS) analysis revealed the existence of stigmasterol (1.2%), stigmastane3, 6 dione,-5a (2.2%), betulin (8.4%), eicosanoic acid (1.09%), glycerol 1 palmitate (20.72%), ascorbyl palmitate (0.92%) and triamcinolone acetonide (0.89%) in both the extracts and effective in diabetes management.